OPTIMALISASI STRATEGI PENERIMAAN MAHASISWA BARU MELALUI METODE REGRESI LINEAR - Juliani, Fitri; Ade Irwanda, Ahmad (Smart Education, 2025)
New Student Admissions (PMB) is a strategic activity that plays an important role in determining the growth, sustainability, and competitiveness of a university. Lancang Kuning University (UNILAK) as one of the private universities in Riau Province faces the challenge of maintaining the stability of the number of applicants while increasing the effectiveness of its student admission strategy. This study aims to optimize the PMB strategy by applying a simple linear regression method to predict the number of new students based on historical admission data for the last five years, namely the period 2020/2021 to 2024/2025. The data used consists of the variables of the number of applicants (X) and the number of new students accepted (Y). The analysis results show a regression model of Y=509.94+0.716X with a correlation coefficient (r) of 0.91 and a coefficient of determination (R²) of 0.83, indicating a very strong positive relationship between the two variables. This model was used to predict the number of new students for the next three years, namely 2.561 students in 2025/2026, 2.609 students in 2026/2027, and 2.666 students in 2027/2028. These results show a stable increase of around two percent per year. Thus, the application of the simple linear regression method has proven to be effective in supporting data-based planning and strategic decision-making at Lancang Kuning University.